THE EFFECT OF BRAND AWARENESS AND BRAND ATTITUDE ON CONSUMER PURCHASE INTEREST IN INDIHOME PRODUCTS IN THE TELECOMMUNICATIONS (WITEL) AREA OF MAKASSAR - Nurhikmah, Nurhikma; Ramadhoni, Buyung; nurinaya, nurinaya (Jurnal Ekonomi Balance, 2018)
This research used quantitative with descriptive approach that aims to describe the object of research or research results through data or samples that have been collected, samples in this study as many as 97 respondents. Data collection techniques used are literature research, observation, questionnaires and assisted with documentation to search for actual facts. And the data analysis used in this research is multiple linear regression analysis and descriptive analysis which is used to explain the variable of brand awareness (X1) and brand attitude (X2) to consumer purchase interest variable (Y), and do some testing that is validity test, reliability, partial test, and coefficient of determination test. The results of this research indicated that brand awareness (X1) effect significantly positive towards the consumer interest based on multiple linear regression equation with a significant level of 0.032 < 0.05 and t test results of 2.170 > t table 1.985. Brand attitude (X2) has a positive and significant effect on consumer buying interest based on multiple linear regression equation with significant level 0,001 < 0,05 and result of t test counted 3,540 > t table 1,985.